2019
DOI: 10.1177/1468087419857602
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of water injection in spark-ignition engines using the stochastic reactor model with tabulated chemistry

Abstract: Water injection is investigated for turbocharged spark-ignition engines to reduce knock probability and enable higher engine efficiency. The novel approach of this work is the development of a simulation-based optimization process combining the advantages of detailed chemistry, the stochastic reactor model and genetic optimization to assess water injection. The fast running quasi-dimensional stochastic reactor model with tabulated chemistry accounts for water effects on laminar flame speed and combustion chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…They demonstrated a reduction of more than 80% in NO x emissions at the expense of 20% torque reduction using the water-to-fuel (W/F) ratio of 1 at the engine speed of 4000 rev/min. Franken et al 30 used a generic algorithm to perform simulation-based multi-objective optimization of water injection in a turbocharged spark ignition (SI) engine. They achieved about 12% decrease in fuel consumption compared to that of without water due to increased compression ratio at the W/F ratio of 0.4.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated a reduction of more than 80% in NO x emissions at the expense of 20% torque reduction using the water-to-fuel (W/F) ratio of 1 at the engine speed of 4000 rev/min. Franken et al 30 used a generic algorithm to perform simulation-based multi-objective optimization of water injection in a turbocharged spark ignition (SI) engine. They achieved about 12% decrease in fuel consumption compared to that of without water due to increased compression ratio at the W/F ratio of 0.4.…”
Section: Introductionmentioning
confidence: 99%
“…The two previous special issues illustrated the spectrum of the conference, which ranged from advanced control concepts 14 to application-oriented contributions with on-road vehicle validation, 5 detailed control of the combustion process on a laboratory scale 69 to combustion process simulation. 10…”
mentioning
confidence: 99%
“…The paper selection covers the main topics of the SCC, from advanced control concepts 2-4 to application-oriented papers with on-road vehicle validation 5,6 or detailed engine process control. [7][8][9][10] Innovative sensor and actuator technologies do not only enable greater flexibility in process control but also lead to greater complexity in future drive trains. For better knowledge of the system states, the concept of a ''soft-sensor'' gets a lot of attention, due to the possibility to reduce the hardware complexity and cost.…”
mentioning
confidence: 99%
“…10,13 This extended the in-cycle control approach presented in the contribution of Liu et al 14 Another very important aspect of control development always lies on the process simulation. The contribution of Franken et al 9 presented a stochastic reactor model with tabulated chemistry. It was shown that it can be used for a simulative analysis of innovative combustion principles such as water injection and that it can be executed with low computational costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation